A qualificação profissional nos liceus de ofício de Curitiba: políticas na gestão da vulnerabilidade - Oliveira, Rondinelli Dutra de (2019)
This work is about the offer of professional qualification at the educational public structure of Curitiba city within the scope and specifically to understand the concepts of public policy and social vulnerability. It is necessary to think about the professional qualification offered at the public structure, specifically the Liceu de Ofícios, considering that this professional qualification public policy has a particularity that is essential, since it is inside another specific public policy for people at risk of social vulnerability. In this way, the Liceu de Ofícios is directly related to other public policies such as the national educational policy, in which the legal basis analysis of the professional qualification are defined. The actions and social assistance services have greater visibility at the government agendas discussions, since the creation of the Unique System of Social Assistance and the qualification offers still need a systematic evaluation. Methodologically the research includes a databases review, especially at CAPES / MEC and Scielo journal`s site, a documentary analysis of the applicable legislation, an analysis of the public policies implementation and the management protocol as well as the access to some databases of the liceus management. As a result, the public power actions at the professional qualification conception, as a short training with few informations about the professional activity, classified as free courses. The courses offered are managed for a work in which technology is essentialist with the objective of have access to qualification. The professional education in this area is a non-formal education of variable duration, designed to provide the worker with the basic skills to enable him to become more professional. However, in order to qualify and update himself, this vulnerable subject is destined for a kind of work that is almost always marginal and precarious, and, because of neoliberalism influence, the outsourcing activity places social institutions too in a vulnerability situation. In line with international discussions at ILO (International Labor Organization), Social and Professional Qualification is understood as a right and as an indispensable condition for guaranteeing decent work for men and women with the qualification right in a gradual universalization promotion. Despite the criticism about the precariousness of the training offer, it is necessary to seek a full professional qualification for the vulnerable subjects. Social and Professional Qualification is defined as a qualification that allows the insertion and citizen action at job market, with effective impact at people`s life andwork.